04 “I sámifize it.” Preschool in the Centre of South Sámi Language and Culture Learning in Norway - Heidi Harju-Luukkainen; Karianne Berg; Asbjørn Kolberg (2022)
For an Indigenous population, there is a need for an inclusive educational space from the language and culture srevitalisation perspective. This is especially important during the early years when the basics of the language are formed alongside cultural knowledge. This paper takes a closer look at a South Sámi preschool language learning environment through the lenses of teachers. The South Sámi (South Saami) is the southernmost Sámi population, frequently described as a minority within the minority. The estimation for South Sámi speakers in Norway is around 300, making the language severely endangered This paper aims to take a closer look at how early childhood education teachers describe the South Sámi language learning space in their preschool environment. For this study, in total, three preschool teachers from a South Sámi preschool were interviewed. This textual data were analysed with content analysis. According to the results, the early childhood education in South Sámi context was seen as an important inclusive language and culture srevitalising space with a clear societal responsibility.